Unsur Fisik dan Unsur Batin pada Puisi “Jarak 1” , “Jarak 2”, “Sajak Ziarah 1”, “Sajak Ziarah 2” Karya Heri Isnaini - Defa Rosa Widara; Difa Rosi Widari; Raka Muhammad Arfan Maulana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Poetry is a form of literary expression that contains physical and mental elements. Distance Poem 1, Distance 2, Pilgrimage Poem 1, and Pilgrimage Poem 2 by Heri Isnaini. These four literary works are rich in physical and mental elements, and these two elements complement each other and build meaning. This research aims to analyze how the physical and mental elements in the poem form the meaning and aesthetics of literary works. and the physical elements studied include diction, imagery, language style, rhyme, and typography as an external form of poetry that builds a structure of beauty. Meanwhile, the inner elements analyzed include themes, feelings, tone, and mandates as the core meaning of the poem. The method used is the Literature Study method. Data was collected from written sources such as poetry theory books, scientific articles, and publications that discuss poetry and biographies of poets.